Investigation of Corrosion Product Distribution and Induced Cracking Patterns in Reinforced Concrete Using Accelerated Corrosion Testing - Olfa Loukil; Lucas Adelaide; Véronique Bouteiller; Marc Quiertant; Frédéric Ragueneau; Thierry Chaussadent (Applied Sciences)
The present study investigates the corrosion development and induced cracks in reinforced concrete specimens submitted to an accelerated corrosion test. The accelerated chloride-induced corrosion test was performed using an impressed current mode. Three current densities (50, 100 and 200 µA/cm2 of steel) and different exposure times were considered. The objective of the experiments is to analyse two distinct types of damage: firstly, internal damage near the steel/concrete interface, which can be observed in the distribution of corrosion products, as well as damage within the concrete cover, which manifests as cracking. Secondly, external damage, which can be observed in the form of rust spots and concrete surface cracks. The aim of this analysis is to elucidate the relationship between internal damage and external damage. The study confirmed that the corrosion products are non-uniformly distributed around and along the steel reinforcing bar. It also highlighted that the accelerated corrosion test conditions, such as current density, duration, environmental conditions and the specimen geometry, have a significant influence on the distribution of the corrosion products and their thickness around the steel reinforcement and therefore on the internal and external crack patterns. The data analysis revealed a substantial dispersion and contrast in terms of the data, which precluded the establishment of a definitive correlation between internal and external deterioration.